Analysis of the Digital Recording Process for the Song “Ngemodhi Lalampa” By Kasokan - Hamim Afrian Nurcahyadi (Repertoar, 2026)
Kasokan is an art community that introduces the refined culture of Madura through music, poetry, and clothing with religious elements that are in harmony with Madura, which is famous for its religiosity. The Kasokan community has produced songs, one of which is “Ngemodhi Lalampa,” which they recorded using home recording equipment. This study aims to analyze the recording process carried out by the Kasokan community, including the types of equipment used, obstacles encountered during the music recording process, and the smart solutions applied. This study uses a descriptive qualitative approach with data collection methods through observation, interviews, and documentation. The findings show that the recording process was carried out in stages using limited equipment, referring to the theory of the recording process and recording equipment. Despite facing various technical limitations, the Kasokan community was still able to carry out the recording process well and produce quality work.